2010
DOI: 10.1038/nature08947
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic organization of sensory input to cortical neurons in vivo

Abstract: In sensory cortex regions, neurons are tuned to specific stimulus features. For example, in the visual cortex, many neurons fire predominantly in response to moving objects of a preferred orientation. However, the characteristics of the synaptic input that cortical neurons receive to generate their output firing pattern remain unclear. Here we report a novel approach for the visualization and functional mapping of sensory inputs to the dendrites of cortical neurons in vivo. By combining high-speed two-photon i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

39
411
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 487 publications
(451 citation statements)
references
References 39 publications
39
411
1
Order By: Relevance
“…The existence of feature-locked and featurevariant networks may explain why some studies found more variability than others in the tuning of dendritic input sites of layer 2/3 pyramidal cells (6)(7)(8) and may suggest that variability is likely due to inputs from deeper cortical layers. The combination of distinct layer modules in feature-variant networks is consistent with previous studies in brain slices showing cross-talk between different subnetworks in layer 2/3 and layer 5 (18,19).…”
mentioning
confidence: 99%
“…The existence of feature-locked and featurevariant networks may explain why some studies found more variability than others in the tuning of dendritic input sites of layer 2/3 pyramidal cells (6)(7)(8) and may suggest that variability is likely due to inputs from deeper cortical layers. The combination of distinct layer modules in feature-variant networks is consistent with previous studies in brain slices showing cross-talk between different subnetworks in layer 2/3 and layer 5 (18,19).…”
mentioning
confidence: 99%
“…Two-photon raster scanning microscopy with galvanometric Svoboda et al, 1999) or resonant (Jia et al, 2010) mirrors is probably the most widespread approach for the functional investigation of brain circuits with cellular resolution. In terms of temporal resolution, scanning microscopes based on galvanometric mirrors reach a maximal full-frame acquisition speed of a few Hz (Helmchen and Denk, 2005), and resonant scanningbased systems achieve ∼30 Hz (Jia et al, 2010).…”
Section: Scanning and Scanless Imaging Of Neuronal Networkmentioning
confidence: 99%
“…In terms of temporal resolution, scanning microscopes based on galvanometric mirrors reach a maximal full-frame acquisition speed of a few Hz (Helmchen and Denk, 2005), and resonant scanningbased systems achieve ∼30 Hz (Jia et al, 2010). Smart movements of the mirrors over specific trajectories can significantly increase the acquisition speed up to 100 Hz (Lillis et al, 2008).…”
Section: Scanning and Scanless Imaging Of Neuronal Networkmentioning
confidence: 99%
“…Somatic signals provide intrinsic information about cell firing, while local, synaptic signals inform about the spatial and functional connectivity of the network and its activation state. Indeed, the computational ability of a neuron’s dendrites is intimately tied to and ultimately informed by presynaptic inputs, whose activity leads to discernable behavioral functions postsynaptically (Jia et al, 2010). In hippocampal and neocortical pyramidal neurons, neighboring dendritic synapses are more likely to be activated synchronously than synapses spaced further apart (Kleindienst et al, 2011; Takahashi et al, 2012).…”
Section: Dendritic Structure and Synaptic Integration Of Presynaptic mentioning
confidence: 99%
“…The spatial targeting of motoneuron or interneuron dendrites and the integration of synaptic inputs conferring rhythmicity have yet to be defined, but dendritic filopodial activity follows a topographic pattern that maps (Kishore and Fetcho, 2013) onto their recruitment order (McLean et al, 2007) and subsequent electrical activity level, delineating behavioral function to dendrites located in discrete regions along the dorso-ventral axis. Thus, the location and targeting of specific dendritic subregions by spatially defined presynaptic neurons may suggest a functional role for individual dendritic branches (Wei et al, 2001; Poirazi et al, 2003; Branco and Häusser, 2010), or perhaps even synapses (Jia et al, 2010), in the output of a given motor neuron.…”
Section: Dendritic Structure and Synaptic Integration Of Presynaptic mentioning
confidence: 99%